Atomic migration strategy for web teams - Harnisch, Harrison; Womersley, Katie (O'Reilly Media, 2018)
How do you turn an application riddled with technical debt into a scalable codebase that's beautiful, clean, and productive? With this practical ebook, Harrison Harnisch and Katie Womersley of the Buffer social media management platform show you how to successfully rewrite and migrate your application using Atomic Design. In the process, you'll discover how breaking your application into basic components makes a rewrite much more efficient. Atomic Design, created by web designer and consultant Brad Frost, is a system for working with the fundamental building blocks--the atoms--of modern web interfaces. This guide provides hands-on instructions for stitching these simple components together to rewrite your application in a low-risk and nondisruptive way. While the ebook's examples focus on migrating a frontend application, you can also use these techniques for mobile and backend applications. Determine if your existing application requires a rewrite Explore how the Atomic Design system breaks up complex interfaces into discrete pieces that you can focus on one at a time Learn when to perform a synchronous versus an asynchronous code migration Get step-by-step instructions for using Atomic Design to perform an asynchronous rewrite Build a compelling business case for rewriting your application, and structure a team for undertaking the project.